13
$\begingroup$

$\displaystyle \sum_{n=i}^{\infty} {2n \choose n-i}^{-1}=\sum_{n=i}^{\infty} \frac {1}{{2n \choose n-i}}$ is a very interesting one. Here is what I have from WolframAlpha.

$$\displaystyle \sum_{n=0}^{\infty} {2n \choose n}^{-1}=\frac{2}{27}(18+\sqrt{3}\pi)$$

$$\displaystyle \sum_{n=1}^{\infty} {2n \choose n}^{-1}=\frac{1}{27}(9+2\sqrt{3}\pi)$$

$$\displaystyle \sum_{n=1}^{\infty} {2n \choose n-1}^{-1}=\frac{1}{27}(9+5\sqrt{3}\pi)$$

For $i \geq 2$, WA just comes up with closed forms involving generalised hypergeometric functions. Here is one example. I would conjecture that this is still in fact expressible in terms of the sort of form we see above but I have no clue about hypergeometric functions so I was hoping somebody could enlighten me. Also, it looks like some sort of computational artefact of not being able to start the sum at $n=1$. It seems to give a natural, consistent form for the first two cases ($i=0,1$), and when asking WA to sum it in the case $i=1$, but starting from $n=2$, it uses a hypergeometric function in the answer, whereas we know the answer should in fact be $\frac{1}{27}(-18+5\sqrt{3}\pi)$.

Also, could anybody come up with a (more elementary i.e. anything not involving special functions) proof of the formula $\displaystyle \sum_{n=1}^{\infty} {2n \choose n}^{-1}=\frac{1}{27}(9+2\sqrt{3}\pi)$?

I have struggled and failed, and this is the part I would most like answered if possible.

Thanks, and good luck (if needed).

$\endgroup$
  • $\begingroup$ The fact that you have $2\sqrt{3}\pi$ appearing in your sums tells me that the Gamma function is needed to evaluate these sums. I would guess that there is not a more elementary way to prove your equalities. $\endgroup$ – graydad Nov 13 '14 at 21:44
  • $\begingroup$ I can handle a Gamma I think if necessary $\endgroup$ – ShakesBeer Nov 13 '14 at 21:45
  • $\begingroup$ Are you not considering the Gamma function to be a special function? $\endgroup$ – graydad Nov 13 '14 at 21:46
  • $\begingroup$ Here is an "elementary" demonstration of the basic result: math.stackexchange.com/questions/548563/… $\endgroup$ – Ron Gordon Nov 13 '14 at 21:58
  • $\begingroup$ @graydad the gamma is really pretty important and useful in higher mathematics. It is a special function, but at the same time the only one I'm not ruling out. $\endgroup$ – ShakesBeer Nov 13 '14 at 22:01
6
$\begingroup$

Generating Function for the Reciprocals of the Central Binomial Coefficients

Using the fact that $$ \frac{4^n}{\binom{2n}{n}} =\frac{n}{n-\frac12}\frac{4^{n-1}}{\binom{2n-2}{n-1}}\tag{1} $$ we can compute the generating function for the reciprocals of the central binomial coefficients: $$ \begin{align} \frac{4^n}{\binom{2n}{n}} &=\prod_{k=1}^n\frac{k}{k-\frac12}\\ &=\frac{\Gamma(n+1)}{\Gamma(1)}\frac{\Gamma(\frac12)}{\Gamma(n+\frac12)}\\ &=n\,\mathrm{B}(n,\tfrac12)\\ &=n\int_0^1(1-t)^{n-1}t^{-1/2}\,\mathrm{d}t\\ &=2n\int_0^1(1-t^2)^{n-1}\,\mathrm{d}t\\ \frac{x^n}{\binom{2n}{n}} &=\frac{nx}2\int_0^1\left(\frac{x(1-t^2)}4\right)^{n-1}\,\mathrm{d}t\\ \sum_{n=1}^\infty\frac{x^n}{\binom{2n}{n}} &=\frac{x}2\int_0^1\frac1{\left(1-\frac{x(1-t^2)}4\right)^2}\,\mathrm{d}t\\ &=\frac{8x}{(4-x)^2}\int_0^1\frac1{\left(1+\frac{x}{4-x}t^2\right)^2}\,\mathrm{d}t\\ &=\frac{8x^{1/2}}{(4-x)^{3/2}}\int_0^{\sqrt{\frac{x}{4-x}}}\frac1{\left(1+t^2\right)^2}\,\mathrm{d}t\\ &=\frac{4x^{1/2}}{(4-x)^{3/2}}\left[\frac{t}{1+t^2}+\tan^{-1}(t)\right]_0^{\sqrt{\frac{x}{4-x}}}\\ &=\frac{x}{4-x}+\frac4{4-x}\sqrt{\frac{x}{4-x}}\tan^{-1}\left(\sqrt{\frac{x}{4-x}}\right)\\ \sum_{n=0}^\infty\frac{x^n}{\binom{2n}{n}} &=\frac4{4-x}\left[1+\sqrt{\frac{x}{4-x}}\tan^{-1}\left(\sqrt{\frac{x}{4-x}}\right)\right]\\ &=\frac4{4-x}\left[1+\sqrt{\frac{x}{4-x}}\sin^{-1}\left(\frac{\sqrt{x}}2\right)\right]\tag{2} \end{align} $$ Plug in $x=1$ and we get $$ \begin{align} \sum_{n=0}^\infty\frac1{\binom{2n}{n}} &=\frac43\left[1+\sqrt{\frac13}\sin^{-1}\left(\frac12\right)\right]\\ &=\frac43+\frac{2\pi}{9\sqrt3}\tag{3} \end{align} $$


Extending the Previous Result

Suppose we have $$ F_k(x)=\sum_{n=k}^\infty\frac{x^{n-k}}{\binom{2n}{n-k}}\tag{4} $$ $F_0(x)$ is given in $(2)$ above.

We can use the identity $$ \binom{2n}{n-k-1}=\frac{n-k}{n+k+1}\binom{2n}{n-k}\tag{5} $$ to get $$ \begin{align} \frac1{\binom{2n}{n-k-1}}-\frac1{\binom{2n}{n-k}} &=\frac1{\frac{n-k}{n+k+1}\binom{2n}{n-k}}-\frac1{\binom{2n}{n-k}}\\ &=\frac1{n-k}\left[\frac{n+k+1}{\binom{2n}{n-k}}-\frac{n-k}{\binom{2n}{n-k}}\right]\\ &=\frac{2k+1}{n-k}\frac1{\binom{2n}{n-k}}\tag{6} \end{align} $$ Equation $(6)$ shows that $$ \frac{\mathrm{d}}{\mathrm{d}x}(xF_{k+1}(x)-F_k(x))=\frac{2k+1}{x}(F_k(x)-1)\tag{7} $$ Formula $(7)$ gives us a way to compute $F_{k+1}$ from $F_k$, via integration.


Example

If we let $x=4\sin^2(\theta)$, then $$ \begin{align} &\int\frac{F_0(x)-1}{x}\mathrm{d}x\\ &=\int\left[\frac1{4-x}+\frac4{4-x}\sqrt{\frac1{x(4-x)}}\sin^{-1}\left(\frac{\sqrt{x}}2\right)\right]\mathrm{d}x\\ &=\int\left[\frac1{4\cos^2(\theta)}+\frac1{\cos^2(\theta)}\sqrt{\frac1{16\sin^2(\theta)\cos^2(\theta)}}\,\,\theta\right]8\sin(\theta)\cos(\theta)\,\mathrm{d}\theta\\[3pt] &=2\int\left[\tan(\theta)+\theta\sec^2(\theta)\right]\mathrm{d}\theta\\[12pt] &=2\theta\tan(\theta)-1\\[9pt] &=2\sqrt{\frac{x}{4-x}}\sin^{-1}\left(\frac{\sqrt{x}}2\right)-1\tag{8} \end{align} $$ where the constant of integration was chosen because $xF_1(x)-F_0(x)=-1$ at $x=0$.

Thus, we get $$ xF_1(x)-F_0(x)=2\sqrt{\frac{x}{4-x}}\sin^{-1}\left(\frac{\sqrt{x}}2\right)-1\tag{9} $$ Therefore, $$ F_1(x)=\frac1{4-x}+\frac{12-2x}{4-x}\frac1{\sqrt{x(4-x)}}\sin^{-1}\left(\frac{\sqrt{x}}2\right)\tag{10} $$ Plug in $x=1$ and we get $$ \sum_{n=1}^\infty\frac1{\binom{2n}{n-1}}=\frac13+\frac{5\pi}{9\sqrt3}\tag{11} $$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ I hope using the Beta and Gamma functions is okay. Since Jack D'Aurizio used them (explicitly and implicitly), I assumed it would be okay. $\endgroup$ – robjohn Nov 14 '14 at 16:15
  • $\begingroup$ No I don't mind, thanks for the effort in fact. I just think that at this point in time it was a little unnecessary, given the answers. But thanks :) $\endgroup$ – ShakesBeer Nov 14 '14 at 16:23
  • $\begingroup$ I think that different approaches, no matter how many one already has, can be useful. The ideas used in each approach may be helpful in other problems. $\endgroup$ – robjohn Nov 14 '14 at 16:26
  • $\begingroup$ well to me it's essentially the same approach. The tricks are just that, tricks. Still, you get the accept now :) $\endgroup$ – ShakesBeer Nov 14 '14 at 18:25
  • $\begingroup$ I believe they are basically different approaches. I am computing the generating function of $\binom{2n}{n-k}$ as a sequence in $n$ for $k=0,1,\dots$. We plug in $x=1$ to get the sums you are interested in. Robert Israel is computing the generating function of $\sum\limits_{n=k}^\infty\binom{2n}{n-k}$ as a sequence in $k$. We look at the coefficients of $t^k$ to get the sums you are interested in. $\endgroup$ – robjohn Nov 14 '14 at 18:46
5
$\begingroup$

$$\sum_{n=0}^{+\infty}\binom{2n}{n}^{-1}=\sum_{n\geq 0}(2n+1)\frac{\Gamma(n+1)^2}{\Gamma(2n+2)}=\sum_{n\geq 0}\int_{0}^{1}(2n+1)(x(1-x))^n\,dx$$ hence: $$\sum_{n=0}^{+\infty}\binom{2n}{n}^{-1}=\int_{0}^{1}\frac{1+x(1-x)}{(1-x(1-x))^2}\,dx$$ and the integral can be easily evaluated through the residue theorem. Other cases are similar.

| cite | improve this answer | |
$\endgroup$
  • 1
    $\begingroup$ +1, when Gamma function was mentioned in the comments, I began waiting for your answer :) $\endgroup$ – Petite Etincelle Nov 13 '14 at 23:29
  • 3
    $\begingroup$ I was just hovering over the accept button... it's a bit mean, but I think you need a couple more details. $\endgroup$ – ShakesBeer Nov 14 '14 at 0:17
3
$\begingroup$

We can do an example to see how this calculation actually works. Suppose we seek to evaluate $$\sum_{n\ge 4} {2n\choose n-4}^{-1}.$$

This is $$\sum_{n\ge 4} \frac{(n-4)! \times (n+4)!}{(2n)!} = \sum_{n\ge 4} \frac{\Gamma(n-3) \times \Gamma(n+5)}{\Gamma(2n+1)} \\ = \sum_{n\ge 4} (2n+1) \frac{\Gamma(n-3) \times \Gamma(n+5)}{\Gamma(2n+2)} = \sum_{n\ge 4} (2n+1) \mathrm{B}(n+5, n-3).$$

Recall the beta function integral $$\mathrm{B}(x,y) = \int_0^\infty \frac{t^{x-1}}{(1+t)^{x+y}} dt.$$

This gives for the sum the representation $$\int_0^\infty \sum_{n\ge 4} (2n+1) \frac{t^{n+4}}{(1+t)^{2n+2}} dt = \int_0^\infty \frac{t^4}{(1+t)^2} \sum_{n\ge 4} (2n+1) \frac{t^{n}}{(1+t)^{2n}} dt \\ = \int_0^\infty \frac{t^4}{(1+t)^2} \times \frac{(9t^2+11t+9)t^4}{(1+t)^6(t^2+t+1)^2} dt \\ = \int_0^\infty \frac{(9t^2+11t+9)t^8}{(1+t)^8(t^2+t+1)^2} dt.$$

This integral can be evaluated by considering $$f(z) = \log z \times \frac{(9z^2+11z+9)z^8}{(1+z)^8(z^2+z+1)^2}$$ evaluated on a keyhole contour with the slot on the positive real axis and the branch cut of the logarithm also on that axis, traversed counterclockwise.

There are four segments: $\Gamma_1$ just above the cut, $\Gamma_2$ the large circle of radius $R$, $\Gamma_3$ the segment below the cut and $\Gamma_4$ the small circle around the origin of radius $\epsilon$.

Using $$|\log(Me^{i\theta})| = |\log M + i\theta| = \sqrt{(\log M)^2+\theta^2}$$ we obtain that the contribution along $\Gamma_2$ is $$2\pi R \times \log R / R^2 \to 0$$ as $R\to \infty,$ so it vanishes.

The contribution along $\Gamma_4$ is $$2\pi\epsilon \times |\log \epsilon| \times \epsilon^8 \to 0$$ as $\epsilon\to 0,$ so it vanishes as well.

We get two contributions from the logarithm below the positive real axis along $\Gamma_3$, one of which cancels the integral along $\Gamma_1$ and the other one of which is $$-2\pi i \int_0^\infty \frac{(9t^2+11t+9)t^8}{(1+t)^8(t^2+t+1)^2} dt$$ i.e. the integral we are trying to calculate.

Let $\rho_0 = -1$ and $$\rho_{1,2} = -\frac{1}{2} \pm \frac{\sqrt{3}i}{2}.$$ We thus have that by the Cauchy Residue Theorem applied to the keyhole contour $$\int_0^\infty \frac{(9t^2+11t+9)t^8}{(1+t)^8(t^2+t+1)^2} dt = - (\mathrm{Res}_{z=\rho_0} f(z) + \mathrm{Res}_{z=\rho_1} f(z) + \mathrm{Res}_{z=\rho_2} f(z)). $$

Now to calculate these residues we use a CAS but it will need some assistance namely from the expansion about $\rho$ $$\log z= \log(\rho + z -\rho) = \log\rho + \log (1 + (z-\rho)/\rho) = \log\rho + \sum_{q\ge 1} \frac{(-1)^{q+1}}{q} \frac{(z-\rho)^q}{\rho^q}.$$

We use this expansion to compute the residues, making sure that the constant term $\log\rho$ agrees with the chosen branch.

This gives for the first residue that $$\mathrm{Res}_{z=\rho_0} f(z) = \frac{57}{20} - 3\pi i$$ and for the second $$\mathrm{Res}_{z=\rho_1} f(z) = \frac{1}{3} + \frac{23\pi \sqrt{3}}{27} + \pi i -\frac{1}{3}\sqrt{3}i$$ and for the third $$\mathrm{Res}_{z=\rho_2} f(z) = \frac{1}{3} - \frac{46\pi \sqrt{3}}{27} + 2\pi i +\frac{1}{3}\sqrt{3}i.$$

Adding these and negating the result we finally have $$\frac{23\pi\sqrt{3}}{27} - \frac{211}{60}.$$

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

Using Maple, I also get $$ \sum _{n=2}^{\infty } {2\,n\choose n-2} ^{-1}={\frac { 23}{6}}-{\frac {13\,\pi \,\sqrt {3}}{27}} $$ $$\sum _{n=3}^{\infty } {2\,n\choose n-3} ^{-1}=\dfrac34+{ \frac {2\,\pi \,\sqrt {3}}{27}} $$ For $i=4$ Maple can't seem to simplify $$\sum _{n=4}^{\infty } {2\,n\choose n-4} ^{-1}= {\mbox{$_3$F$_2$}(1,1,9;\,9/2,5;\,1/4)} $$ but numerically it appears that the answer is $$- \dfrac{211}{60}+\dfrac{23 \pi \sqrt{3}}{27}$$ for $i=5$ it is $$ \dfrac{6169}{840}-\dfrac{31 \pi \sqrt{3}}{27}$$ and for $i=6$ it is $$ {\frac {1709}{2520}}+{\frac {2\,\pi \,\sqrt {3}}{27}}$$ etc. The coefficient of $\sqrt{3} \pi/27$ seems to have the generating function $${\frac {6\,t-6}{ \left( {t}^{2}+t+1 \right) ^{2}}}+{\frac {-5\,t+8}{{t }^{2}+t+1}} $$

EDIT: Ah! Using Jack's method, the generating function for this sequence turns out to be

$$ \eqalign{ \sum_{i=0}^\infty t^i \sum_{n=i}^\infty {2n \choose n-i}^{-1} &= \sum_{i=0}^\infty t^i \sum_{n=i}^\infty \int_0^1 (n+i) t^{n-i} (1-t)^{n+i-1}\; dt\cr =&\dfrac{\ln((1+\sqrt{t})/(1-\sqrt{t})) (t+1) t^{3/2}}{(t^2+t+1)^2} - \dfrac{ \ln(1-t) (t^2 + 3 t + 1) t}{2(t^2+t+1)^2}\cr & - \dfrac{(5 t^3 - 3 t^2 - 9 t - 2) \pi \sqrt{3}}{27 (t^2 + t + 1)^2} + \dfrac{1-t}{3 (t^2 + t + 1)} - \dfrac{1}{t-1} - 1 }$$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ I used Maple's gfun package. But for the full generating function, I interchanged sums and integral. $\endgroup$ – Robert Israel Nov 14 '14 at 0:07
  • $\begingroup$ Something seems wrong in that first term - won't $\ln(1+\sqrt{t}/1-\sqrt{t})$ have an even expansion in terms of $\sqrt{t}$ (and thus be expressible in terms of integral powers of $t$)? That's a little problematic since it's being multiplied by $t^{3/2}$... $\endgroup$ – Steven Stadnicki Nov 14 '14 at 1:23
  • 1
    $\begingroup$ No, $\ln\left(\dfrac{1+s}{1-s}\right)$ is an odd function of $s$, so $\ln((1+\sqrt{t})/(1-\sqrt{t})) t^{3/2}$ will have an expansion in positive integer powers of $t$. $\endgroup$ – Robert Israel Nov 14 '14 at 3:17
  • $\begingroup$ Ahhh, of course - I should have been able to see that from the definition (it's of the form $f(s)-f(-s)$, so reverses sign when the sign of $s$ reverses), but somehow in actually trying to do the subtraction I got tangled. Mea culpa! $\endgroup$ – Steven Stadnicki Nov 14 '14 at 4:13
  • $\begingroup$ I think this is perhaps my favourite method, although getting a closed form from that for general $i$ seems hardly like an appealing job! $\endgroup$ – ShakesBeer Nov 14 '14 at 9:16
2
$\begingroup$

The basic result is $~\displaystyle\sum_{n=1}^\infty\frac{(2x)^{2n}}{\displaystyle{2n\choose n}n^2}=2\arcsin^2x.~$ By repeating the process of differentiation

and multiplication twice, and letting $x=\dfrac12,~$ you will obtain a closed form for your series.

Then, by using similar means, try deducing a general formula for each modified version of

this initial result, for $i>0$, namely, $i=1,2,3$, etc. If WA does not return nice results, use

FullSimplify[...].

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ This is what I had first thought of when somebody mentioned this sereis. Using integration by parts. Worth mentioning, I think, although not all that elegant $\endgroup$ – ShakesBeer Nov 14 '14 at 9:13

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.